Biological characteristics of Sycanus croceovitatus Dohrn. (Reduviidae, Hemiptera) - Thanh, Nguyen Xuan; Kieu Khanh, Bui Thi (Academia Journal of Biology, 2014)
Sycanus croceovitatus Dohrn (Reduviidae Hemiptera) is a large bug, one of the most important natural enemy species of lepidopteran insect pests on the litchi (larva of loopers, rollers and moths). At the temperature of 28.5-31oC and air-humidity of 79-85%, its mean life cycle lasts 66.76 ± 0.75 days; the egg period lasts 15.02 ± 0.47 days; the larva period lasts 41.34 ± 1.10 days; the period from the larva last cast to the first egg laying of the adult lasts 10.40 ± 0.68 days. Whereas, at the temperature of 18.5-23.2oC and air-humidity of 71-82%, its mean life cycle lasts 182.02 ± 2.30 days; the egg period lasts 24.88 ± 2.35 days; the larva period lasts 139.58 ± 3.55 days and the adult females begin to lay eggs after 17.56 ± 1.00 days from the larva last cast.